2019
DOI: 10.1039/c8ee02662a
|View full text |Cite
|
Sign up to set email alerts
|

Efficient CO2 to CO electrolysis on solid Ni–N–C catalysts at industrial current densities

Abstract: We demonstrate the direct electrochemical conversion of CO2 to CO using solid state Ni–N–C carbon catalysts characterized by a coordinative molecular Ni–Nx active moiety at industrial current densities of up to 700 mA cm−2 with faradaic efficiencies superior to those of the state-of-the-art AgOx electrocatalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
370
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(383 citation statements)
references
References 49 publications
12
370
0
1
Order By: Relevance
“…X-Ray Diffraction (XRD) patterns for the 5 catalysts are shown in Figure S1, showing an amorphous character of the materials. Similar to previous works, [30,32] we observed that on the samples prepare at temperatures � 900°C there are nanoparticles embedded in the carbon structure, which makes them difficult to be removed via acid leaching. In addition, residual crystalline inorganic Fe x S y species, namely pyrrhotite and pyrite, can be detected on the catalysts prepared at higher temperatures.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…X-Ray Diffraction (XRD) patterns for the 5 catalysts are shown in Figure S1, showing an amorphous character of the materials. Similar to previous works, [30,32] we observed that on the samples prepare at temperatures � 900°C there are nanoparticles embedded in the carbon structure, which makes them difficult to be removed via acid leaching. In addition, residual crystalline inorganic Fe x S y species, namely pyrrhotite and pyrite, can be detected on the catalysts prepared at higher temperatures.…”
Section: Resultssupporting
confidence: 88%
“…To understand the differences in selectivity, we turn to the different N functionalities. Consistently, experimental studies on NiNC catalysts containing exclusively NiN 4 reported faradaic efficiency up to 99 % towards CO. [32] Therefore, the difference in catalytic activity of our tested materials can be attributed mainly to the concentration of FeN x sites, which are not only the predominant active sites on MNC catalysts, but they are also highly selective in reducing CO 2 to CO. [26,27] In our study however, a lower concentration of pyridinic N correlates with a higher selectivity towards the CO2RR.…”
Section: Resultsmentioning
confidence: 91%
“…The Jaouen and Fontecave groups demonstrated that the Fe nanoparticle, which is inevitably formed during the preparation for FeN 4 , directly correlates to the HER and decreases CO selectivity due to its favorable proton reduction feature (Figure D) . In the case of Ni‐N‐C, Ni centers binding with more than one vacancy, that is, coordinated unsaturated state, stronger *COOH bindings than the NiN 4 site by DFT calculations (Figure E) . Practically, it was further suggested that intentionally synthesized Ni with a 3 N coordination (Ni‐CTF) exhibited higher activity toward CO production than the Ni with a 4N coordination (Ni‐TPP) (Figure F) .…”
Section: Carbon‐based Materialsmentioning
confidence: 98%
“…However, it was recently reported that when Ni is coordinated with defective carbon or with nitrogen doped graphene, HER can be suppressed and as a result CO 2 RR can be promoted in these catalysts. For instance, Ni–N 4 –C active sites were reported to display very high FE CO > 90% at moderate overpotentials, whereas Ni–N coordinated with single and double vacancy in nickel–nitrogen–graphene catalyst can generate CO with a selectivity of 97% . In fact, by tuning the coordination number of Ni, the electron transfer from the active sites to CO 2 reactants is improved and this allows the attainment of high FE CO of 97% at low applied overpotential of merely 0.61 V .…”
Section: Active Sites In Metal‐carbon Catalystsmentioning
confidence: 99%